2017
DOI: 10.1111/dom.13034
|View full text |Cite
|
Sign up to set email alerts
|

A novel GIP analogue, ZP4165, enhances glucagon‐like peptide‐1‐induced body weight loss and improves glycaemic control in rodents

Abstract: Aim: To investigate the effects of the novel glucose-dependent insulinotropic polypeptide (GIP) analogue, ZP4165, on body weight and glycaemic control in rodents, and to investigate if ZP4165 modulates the anti-obesity and anti-hyperglycaemic effects of a glucagon-like peptide-1 (GLP-1) agonist (liraglutide). Methods:The acute insulinotropic effect of ZP4165 was investigated in rats during an oral glucose tolerance test. The long-term effects of ZP4165 on body weight and glycaemic control, either alone or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 24 publications
5
66
0
1
Order By: Relevance
“…The present study is a human proof-of-concept study based on promising rodent studies showing synergistic energy intake and body weight-lowering effects from co-activation of the GIP and GLP-1 receptors, compared with GLP-1 alone [7][8][9]. The clinical data from the present study contrast these rodent findings.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The present study is a human proof-of-concept study based on promising rodent studies showing synergistic energy intake and body weight-lowering effects from co-activation of the GIP and GLP-1 receptors, compared with GLP-1 alone [7][8][9]. The clinical data from the present study contrast these rodent findings.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, studies with GIP infusions have not revealed any independent effects on appetite, energy intake or REE in humans [6]. Surprisingly, rodent data have shown that GIP and GLP-1 receptor co-activation elicits a synergistic effect with regard to energy intake: potentiating the satiety-promoting and body weight-reducing effects of GLP-1 [7][8][9]. The interest in GIP and GLP-1 receptor coactivation emerged when Finan and colleagues showed, in diet-induced obese mice, that co-administration of GIP and GLP-1 receptor agonists decreased body weight and energy intake to a greater extent than that elicited by either agonist alone [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While insulinotropic effects of GIP are well defined, controversy exists regarding its weight-lowering potential. Surprisingly, the pharmacological targeting of the GIP receptor (GIPR) by agonists (130,(136)(137)(138) as well as by antagonists (139,140) led to body weight loss in obese rodents. Notably, a recent study aimed at disentangling these contradictory observations by comparing the in vivo potency of several structurally diverse GIPR agonists with a potent long-acting antagonist (138).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…Recent preclinical studies have shown that co‐administration or combination therapy with analogues of GIP and other gut hormones and/or analogues (e.g. GLP‐1) leads to improved metabolic outcomes . However, the development of combination therapies would not be perceived as being straightforward, especially concerning optimization of the most effective dose and suitable pharmaceutical formulation.…”
Section: Therapeutic Role For Gip In Human Type 2 Diabetesmentioning
confidence: 99%